Surgical Management of Familial Trigeminal Neuralgia With Different Inheritance Patterns: A Case Report - Cervera-Martinez, Claudia; Martinez-Manrique, Jose J.; Revuelta-Gutierrez, Rogelio (Frontiers in Neurology, 2018)
Abstract Introduction: Trigeminal neuralgia (TN) is a disorder characterized by unilateral electric shock-like pain, distributed in one or more trigeminal nerve branches and triggered by usually innocuous stimuli. Amongst the few case reports and literature reviews on familial trigeminal neuralgia, the results of several suggest the involvement of genes associated with biochemical alterations or atherosclerotic vascular malformations. Background: We present four cases of familial trigeminal neuralgia (FTN) within two families (Family A: two brothers; Family B: two sisters). All patients were submitted to surgical treatment by the same surgeon. Discussion: Cases 1 and 2 (family A) exhibited FTN with an uncommon autosomal recessive pattern and clinical features consistent with previous literature reviews and case reports. However, in cases 3 and 4 (family B) we found FTN with a dominant autosomal pattern and an unusual physiopathology characterized by arachnoid adhesions. Conclusion: We conclude, in this case report, that there are several inheritance patterns as well as physiopathology that may be involved in FTN, and that both patterns described in our reported cases were successfully managed with surgery.